Erythroderma secondary to chronic plaque psoriasis: A case report (Indian Journal of Case Reports, 2025)
Erythroderma is characterized by erythema with a variable degree of scaling, which is a rare and often potentially life-threatening condition. A case of a 60-year-old female patient with erythroderma secondary to chronic plaque psoriasis is presented here. Itching, dryness, and irritation were present, and the patient presented with widespread erythematous, scaly plaques. Diabetes mellitus and hepatitis C Virus infections are known to have contributed to the severity of her condition. Systemic corticosteroids, antihistamines, emollients, and supportive care combined with glycemic control constituted treatment. The clinical presentation, diagnostic, and management issues of the disease are illustrated in this case. This case highlights the importance of recognizing and treating erythroderma associated with psoriasis at an early time and with multimodality treatment in patients who are comorbid. Improving outcomes requires routine follow-ups.